Wilayah Udara Indonesia: Sudahkah Kita Memanfaatkannya dan Menjaganya? - Haryono, Harry P. (Indonesian Journal of International Law, 2009)
Controversy always occurs in outerspace discussion where is no official definition of outerspace in any international regulations. The provisions set in Chicago Convention are also not enough to define the meaning of air space of a country and how to use it properly. Still controversy came one after another. In the absence of this provision, State often use other International Convention as an analogy to define their air territory such as UNCLOS 1982. Indonesia as an archipelagic state, who brings the issue of archipelagic state to the Third UN Conference on the Law of the Sea, has done many efforts to ensure their sovereignity over their air space. This article discusses how Indonesia protects its air territory and how far Indonesia explores and exploits benefits from its air space.